Analisis Sentimen Terhadap Dampak Inflasi Menggunakan Naive Bayes - Siti Nurhaliza Sofyan; Muhammad Iqbal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to analyze public sentiment regarding the impact of inflation in 2024 on survival. Inflation is seen as one of the most important factors influencing a country's economic growth. In this research, the results of public sentiment in 300 tweets on the Twitter application were obtained, namely the emotion 'joy' was 194 or 64%, 'surprise' was 71 or 23%, 'fear' was 20 or 6%, 'sadness' was 9 or 3% , 'disgusted' by 7 or 2% and 'angry' by 0.06% . This research uses the orange mining application with multilingual sentiment analysis techniques visualized through box plots and scatter plots, which aims to classify Twitter users based on their emotional responses. The decline in the level of economic growth has led to the emergence of the view that inflation has a negative effect on economic growth, not a positive effect. The findings of this research provide insight into the government's role in overcoming current inflation and providing sustainable benefits and are expected to be used as material for evaluating the government's role.